PEMERINTAH DAN MASYARAKAT DALAM KASUS PENGELOLAAN ADMINISTRASI KEPENDUDUKAN DI UPTD KEPENDUDUKAN DAN PENCATATAN SIPIL KECAMATAN MANDAU KABUPATEN BENGKALIS - SARI, IRENA KURNIA; ", Hassanudin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This study tried to find out the business of government and publicadministration in managing the population in UPTD Population and CivilRegistration Sub-District Saber and understand the factors that influence thegovernment and the community in the management . This research is descriptivequalitative research method . In collecting data the researcher used observation,interview and documentation . By using key informants as a source of informationabout the study .From the data obtained findings , government and community relations inthe management of Population and Civil Registration Administration , the Districtof community participatory planning Saber involved in the process of deliveringthe problems perceived by the public in the stewardship of Population and CivilRegistration Administration . Activity UPTD Population and Civil RegistrationSaber institutional diawasai by the Supervisory Board and the RegionalInspectorate Bengkalis Bengkalis . External oversight of the research conductedby the author Parliament . The Parliament did check the field to obtaininformation and conduct a hearing ( RDP ) and then ask for the report of theOffice of Population and Civil Registration Bengkalis . While the public scrutinyof the activities of Population and Civil Registration UPTD UPTD the Populationand Civil Registration Saber listen to public complaints by opening a complaintbox . In addition to the availability of the website facebook community criticismand suggestions and answer questions about population and civil registrationadministration by staff UPTD Population and Civil Registration .Keywords : Management of Government and Society , Participation ,Transparency , Accountability , Responsiveness on UPTD Population and CivilRegistration .